Randomized controlled trial of resistance exercise and brain aging clocks - Raul Gonzalez-Gomez; Naiara Demnitz; Carlos Coronel; Anne Theil Gates; Michael Kjaer; Hartwig R. Siebner; Carl-Johan Boraxbekk; Agustin M. Ibanez (GeroScience, 2026)
Exercise improves cognition, mental wellbeing, and protects against neurodegeneration. However, most prior neuroscience studies have focused on localized brain changes without quantifying their impact on brain ageing. To quantify the effect of resistance training on brain health using longitudinal assessments. Using resting-state functional magnetic resonance imaging (rs-fMRI) data from 2,433 healthy adults, we trained models to predict brain age and applied them to 309 participants from the Live Active Successful Aging (LISA) randomized trial. Participants in this trial were assigned to one of three groups: heavy-resistance training, moderate-intensity training, or a non-exercise control group. They underwent repeated rs-fMRI and physical fitness assessments at baseline, with follow-up assessments at 1 and 2 years. First, we examined changes in local connectivity between groups. Second, we assessed the impact of resistance training on brain ageing using brain clock models trained on the independent dataset of 2,433 adults. Local analyses revealed increased prefrontal functional connectivity following heavy training, while moderate- and heavy-resistance training significantly reduced brain age (–1.4 to –2.3 years, p FDR < 0.05). These effects emerged at the whole-brain level, rather than within isolated networks such as the default mode, motor, or cerebellar systems. These findings suggest a hierarchical organization of brain aging, driven by distributed network-level changes and expressed through focal regional patterns. Resistance exercise training decelerates brain ageing, as indexed by brain clocks, reinforcing its role as a preventive strategy for brain health.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Fertility impacts in crude oil-contaminated soil based on type and quantity of clay - G. Álvarez-Coronel; V. I. Domínguez-Rodríguez; R. H. Adams; D. J. Palma-López; J. Zavala-Cruz; J. A. Gaspar-Génico (International Journal of Environmental Science and Technology, 2023)

Stabilization and solidification technology for treating heavy oil-contaminated sediments - G. Álvarez-Coronel; V. I. Domínguez-Rodríguez; N. Ovando-García; R. H. Adams (International Journal of Environmental Science and Technology, 2022)

Potato landraces and their wild relatives in 3 micro-centers of diversity in Ecuador: farmers' perception and ecogeography - Á. Monteros-Altamirano; F. Yumisaca-Jiménez; R. Aucancela-Huebla; J. Coronel; L. Corozo-Quiñonez; K. Cunguán (Genetic Resources and Crop Evolution, 2022)

Intrathecal Administration of an Anti‐nociceptive Non-CpG Oligodeoxynucleotide Reduces Glial Activation and Central Sensitization - C. Leiguarda; A. Villarreal; C. Potilinski; T. Pelissier; M. F. Coronel; J. Bayo; A. J. Ramos; A. Montaner; M. J. Villar; L. Constandil; Pablo R. Brumovsky (Journal of Neuroimmune Pharmacology, 2021)

Aβ42 Peptide Promotes Proliferation and Gliogenesis in Human Neural Stem Cells - A. Bernabeu-Zornoza; R. Coronel; C. Palmer; M. Calero; A. Martínez-Serrano; E. Cano; Alberto Zambrano; Isabel Liste (Molecular Neurobiology, 2019)

Water quality indices for groundwater impacted by geogenic background and anthropogenic pollution: case study in Hidalgo, Mexico - D. A. Rivera-Rodríguez; R. I. Beltrán-Hernández; C. A. Lucho-Constantino; C. Coronel-Olivares; S. Hernández-González; M. Villanueva-Ibáñez; V. Nolasco-Arizmendi; G. A. Vázquez-Rodríguez (International Journal of Environmental Science and Technology, 2019)

Diversity and Phenology of Wild Bees in a Highly Disturbed Tropical Dry Forest “Desierto de la Tatacoa”, Huila–Colombia - C A Poveda-Coronel; D Riaño-Jiménez; J R Cure (Neotropical Entomology, 2018)

Daily rhythms in blood and milk lead toxicokinetics following intravenous administration of lead acetate to dairy cows in summer - S. E. Valtorta; M. C. Scaglione; P. Acosta; J. E. Coronel; H. R. Beldomenico; J. C. Boggio (International Journal of Biometeorology, 2006)

DDT and Its Metabolites in Human Milk Collected in Veracruz City and Suburban Areas (Mexico) - V. T. Pardío; S. M. Waliszewski; A. A. Aguirre; H. Coronel; G. V. Burelo; R. M. Infanzon R.; J. Rivera (Bulletin of Environmental Contamination and Toxicology, 1998)

Cadmium and Lead Levels in Cow's Milk from a Milking Region in Santa Fe, Argentine - M. R. Rubio; M. E. Sigrist; T. Encinas; E. E. Baroni; J. E. Coronel; J. C. Boggio; H. R. Beldomenico (Bulletin of Environmental Contamination and Toxicology, 1998)

Non-random deletions in human foamy viruslong terminal repeat during viral infection - J. De Celis-Kosmas; A. Coronel; I. Grigorian; R. Emanoil-Ravier; J. Tobaly-Tapiero (Archives of Virology, 1997)